Advances in ceramic membrane technology: Versatility of fabrication technique, industrial applications, and challenges - Rayane Akoumeh (18560659) (2025)
Ceramic membranes have attracted growing interest in advanced separation and purification processes due to their exceptional chemical and thermal stability. This review provides a concise yet comprehensive overview of key ceramic membrane fabrication techniques. We describe six major approaches – phase inversion, sol–gel processing, electrospinning, dry pressing, slip casting, and extrusion – examining their fundamental mechanisms and critical processing parameters. We discuss how variables such as polymer/ceramic ratios, solvent systems, and sintering conditions affect membrane morphology and performance for each method. The review also highlights a range of applications enabled by ceramic membranes. These include water and wastewater treatment, gas separation, catalytic membrane reactors, biofiltration, pharmaceutical and food processing, and bioprocess engineering. A comparative analysis of fabrication routes is presented, detailing the advantages and limitations of each technique. We then discuss strategies to overcome these challenges: for instance, using low-cost raw materials (clays, fly ash) to reduce cost, optimizing processing to control pore structure, reinforcing membranes for improved strength, and implementing surface modifications or pretreatment to mitigate fouling. Overall, this review elucidates how different manufacturing techniques influence ceramic membrane properties and outlines approaches to address their inherent drawbacks, providing insights into their suitability for industrial separation applications. Other Information Published in: Inorganic Chemistry Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.inoche.2025.114685